Investigating the Impact of Gamified Learning Platforms on Critical Thinking and Problem-Solving Skills in Middle School Students - Nurfadila MY; Suarlin Suarlin; Ali Refaat Ahmed Elsayed (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study investigates the impact of gamified learning platforms on the development of critical thinking and problem-solving skills among middle school students. With the increasing reliance on digital tools, fostering these essential skills has become a critical educational goal. Traditional teaching methods often fail to engage students effectively, which has led educators to explore innovative approaches such as gamified learning. The experimental design of this study involved two groups: an experimental group using gamified learning platforms and a control group following conventional teaching methods. Data were collected through pre-tests and post-tests measuring students' critical thinking and problem-solving abilities. Results indicated that the experimental group showed a significant improvement in both skills, with a 20-point increase in their scores, while the control group exhibited minimal progress. The findings highlight that gamified learning, which integrates game mechanics such as points, rewards, and leaderboards, enhances engagement and motivation, leading to improved cognitive skills. This study emphasizes the potential of gamification to revolutionize educational practices, suggesting that its integration can be a powerful tool to equip students with the necessary skills for the future.